Assessment of COVID-19 pandemic impact on guaranteeing food security in local school catering. (20th October 2021) - Barocco, G; Maggiore, A; Calabretti, A; Bogoni, P; Longo, T
Abstract: Background: The Italian National Institute of Statistics (ISTAT) highlights that in 2020 10% of the Italian population could not afford an adequate meal every 2 days. Families with several children were more affected, for these children school meals represented the only access to a healthy diet. The European Commission Farm to Fork Strategy, concerning the COVID-19 pandemic (CP), underlines the need to act to ensure access to a sufficient supply of affordable food for all. In the Province of Trieste (PT) over 90% of pupils eat in school canteens (12, 000 meals per day). The aims of the project were to verify the impact of CP on the food security of public school canteens (PSC) and determine any Nutritional Critical Points (NCPs) - Corrective Actions (CAs) to guarantee healthy equity meals for all pupils. Methods: The content of Public food procurement and service polices for a healthy diet (PFP) published by the WHO and the Nutrient Analysis Critical Control Points (NACCP) process as indicated by the Ministry of Health were applied. In the first quarter of 2021, all food procurement contracts (n = 6) and all of the school kitchens (n = 45) of PT PSC were verified, the University of Trieste analysed the composition of fresh desserts administered in 7 consecutive weeks. Results: The NACCP process showed NCPs on the low quality of afternoon snacks and on the quantitative/qualitative fat profile of fresh desserts, with a content of 69 to 72% of saturated fat, of 5 to 7% of trans fat and of 8 to 12% oxidized fat as a "dual quality" food. CAs were activated to support all PT PSC in reformulating fresh desserts, as well as in aiding the assessment of the food procurement landscape, activating regular monitoring of compliance and designing procurements adherent to PFP. Conclusions: Project outcomes highlight the importance of taking action to continuously support PSC in order to ensure healthy and equitable food environments for all and to contribute to building a resilient food system. Key messages: Guarantee healthy equity school meals for all pupils by developing on going processes to address the pandemic challenge. Ensure technical assistance to school catering to overcome the impact of COVID–19.